Analisis Penyaluran Produk Prekursor di PT Tri Sapta Jaya Palangka Raya pada Wilayah Kalimantan Tengah - Kaferin, Eggia; Pakereng, Magdalena A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2022)
This research aims to examine the distribution of precursor products in Central Kalimantan. The method of this research is quantitative. This research used a descriptive analysis approach. Technique of data collection is used with documentation. The data analysis used a quantitative descriptive, which aims to describe or depict an object through data collected that have been arranged into simple form. The results of this research reveals that the distribution of the precursor products in 14 regions is normal which helps the firm to distribute the products directly towards the precursor in medics. The highest area or region is Palangka Raya with 4267.5 products and the lowest is Pulang Pisau with 3 products in a period of eight months. The direct distribution applied as the firm's effort to optimize the available resources to satisfy the consumer and retailer in Central Kalimantan